2020
DOI: 10.3390/vaccines8030342
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Evidence-Based Approach to Guiding Effective Influenza Vaccination Policies

Abstract: The availability of several effective and safe vaccines enables health systems to counteract annual influenza epidemics. However, the criteria of appropriateness and sustainability require that each citizen should receive the right vaccine. The value of each vaccine can be assessed within well-known frameworks, such as the Health Technology Assessment (HTA), a step that is fundamental to the process of allocating resources to vaccination strategies. The paper describes how HTA has been incorporated as an evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Public health values would be vital, in particular in disease prevention and health management [ 46 ]. In this regard, the criteria of appropriateness and sustainability seem particularly attractive: each citizen should receive the most appropriate vaccine in order to achieve adequate protection [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Public health values would be vital, in particular in disease prevention and health management [ 46 ]. In this regard, the criteria of appropriateness and sustainability seem particularly attractive: each citizen should receive the most appropriate vaccine in order to achieve adequate protection [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 40 studies included in our systematic review [ 3 , 4 , 5 , 8 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], seven (17.5%) had a non-European perspective and were conducted in Canada ( n = 1) [ 18 ], the USA ( n = 3) [ 19 , 21 , 42 ], China ( n = 1) [ 36 ], Iran ( n = 1) [ 49 ], and low-income countries (LICs) ( n = 1) [ 32 ]; ten (25%) had a global perspective [ 5 , 10 , 12 , 20 , 22 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Among the European studies, eight (36.4%) were conducted specifically in Italy [ 3 , 4 , 13 , 31 , 38 , 39 , 43 , 47 ]. In addition, of the 40 articles included in our work, 17 (42.5%) were systematic reviews or literature reviews [ 3 , 5 , 10 , 11 , 12 , 22 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 37 , 41 , 47 , 48 ], ten (25%) were economic evaluations [ 8 , 13 , 19 , 21 , 23 , 26 , 27 , 34 , 44 , 45 ], seven (17.5%) were cross-sectional studies [ 18 , 35 , 36 , 38 , 42 , 43 , 49 ], two studies (5%) were HTA reports [ 4 , 39 ], one study (2.5%) was a nonlinear regression model [ 33 ], and three studies (7.5%) were expert opinions [ 20 , 40 , 46 ]. The main features of the studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, older adults aged ≥ 65 years could be administered either aQIV, hdQIV, standard-dose egg-based, cell-based, or recombinant SIVs (Italian Ministry of Health, 2022). Although this approach may be justified from the point of view of the vaccine procurement, it may lead to significant between-region differences in vaccination policies 6 (Bonanni et al, 2018;Calabrò et al, 2020). The use of both aQIV (Calabrò et al, 2022) and hdQIV (Cicchetti et al, 2021) in the Italian elderly has recently undergone the process of full health technology assessment (HTA).…”
Section: Introductionmentioning
confidence: 99%